Electrical and spectroscopic analysis in nanostructured SnO2: "long-term" resistance drift is due to in-diffusion - Malagù, Cesare (2011)
A model for conductance in n-type non-degenerate semiconductors is proposed and applied to polycrystalline SnO2 used as a gas sensor. Particular attention is devoted to the fundamental mechanism of Schottky barrier formation due to surface states in nanostructured grains. Electrical and absorption infra-red spectroscopic analysis constitutes strong evidence for oxygen diffusion into the tin oxide grains. The model is then extended to include oxygen in- and out-diffusion. Thus, it is possible to explain the “long-term” resistance drift in oxygen for fully depleted grained samples in terms of tunneling through the double barrier.